Detailed deletion mapping at chromosome 11q23 in colorectal carcinoma - Lee, A S-G (Nature Publishing Group, 2000)
Loss of heterozygosity (LOH) is frequent at the chromosomal region 11q22–q23 in several types of tumours of diverse cell origin. Previous investigations of LOH at this chromosomal region in colorectal carcinoma have been contradictory in their findings, and have only included between 1–4 loci. In order to define any regions of LOH on 11q23, we investigated 16 loci between D11S940 and D11S934 on the long arm of chromosome 11 using microsatellite analysis. Of 57 colorectal carcinomas specimens, 36 (63.2%) demonstrated LOH at one or more marker, with the highest frequencies of LOH at D11S1340 (41.0%), located between 105.13–111.97 Mb from the centromere, and D11S924 (37.1%) and D11S4107 (40.5%), both located approximately 113 Mb from the centromere. No statistically significant associations between LOH and age-of-presentation or Dukes’ stage were found. LOH was observed in colorectal tumours of all Dukes’ stages, including Dukes’ stages A and B, suggesting that the inactivation of a tumour suppressor gene(s) on 11q23 occurs in the early stages of colorectal carcinoma. These results confirm the presence of putative tumour suppressor gene(s) at chromosome 11q23, involved in the carcinogenesis of colorectal carcinoma, and will facilitate future identification of candidate genes. © 2000 Cancer Research Campaign